The Effect of Hip Bracing on Gait in Patients with Medial Knee Osteoarthritis. (25th July 2012) - Wallace, David; Barr, Christa
Abstract : Objective. Impaired hip motion has been associated with heightened medial knee joint loading in patients with knee osteoarthritis (OA). A hip external rotation strap designed to pull the femur into external rotation and abduction may serve as one protective mechanism. The primary aim of our study is to determine if the strap decreases medial knee joint loading during level walking in people with knee OA. Design. This study is a single-day repeated measures design. Methods. 15 volunteers with medial knee OA underwent motion analysis data collection during two randomly assigned walking conditions: (1) wearing the strap and (2) control (no strap). Primary outcome measures were peak pelvis, hip and knee joint motions, and torques. These outcomes were averaged across five trials for each condition. Results. Hip abduction (P < 0.01 ), trunk lean towards the stance limb (P = 0.04 ) and pelvic tilt (P = 0.02 ) significantly increased with the strap versus control trials. Knee adduction loading did not significantly change with the strap (P = 0.33 ). Conclusion. The use of the hip external rotation strap resulted in angular changes at the hip and pelvis which may be beneficial for patients with medial knee osteoarthritis.